Angiotensin-converting enzyme and its clinical significance--a review. Issue 8 (August 1983) - Studdy, P R; Lapworth, R; Bird, R
Abstract : There have been considerable advances in understanding the metabolic role of the endothelial lining cells of the blood vessels. Angiotensin-converting enzyme activity is concentrated in these cells, especially those lining the pulmonary circulation. The enzyme exerts control over systemic vascular tone indirectly through the powerful pressor effect of angiotensin II. A number of therapeutic agents are now available which directly inhibit converting enzyme activity and thereby effect a reduction in blood pressure. Macrophages are the source of increased angiotensin-converting enzyme activity commonly found in association with active sarcoidosis. A better understanding of this phenomenon may give fresh insight into this puzzling condition. Pulmonary endothelial metabolism is affected by lung injury and it is likely that in this situation changing activities of serum angiotensin converting enzyme may indicate the extent of damage and the response to therapy. The full clinical significance of serum ACE measurements has yet to be established. However, raised activities have been reported in a number of other conditions and diabetes mellitus and hyperthyroidism are of particular current interest. The numerous methods and reference ranges described in the literature for the measurement of serum ACE activity require further assessment, and there is a clear need for an accepted reference method.